Online Star vs. Celebrity Endorsements: The Role of Self-Concept and Advertising Appeal in Influencing Purchase Intention - Shi, Pengfei; Lu, Xiaojing; Zhou, Yi; Sun, Chaojing; Wang, Liying; Geng, Biao (Frontiers in Psychology, 2021)
Despite the fact that companies increasingly value online star endorsements as Internet celebrity economy booms, scientific knowledge on the effect of online star endorsements on consumers’ purchase intention is limited. Based on the theories of self and construal level theory, this study investigates the impact of online star vs. celebrity endorsements on purchase intention and explores the underlying mechanism as well as boundary conditions. The results of four studies reveal the following: (1) Compared with no endorsement, both celebrity endorsements and online star endorsements lead to increases in consumers’ purchase intention, with no significant difference between the two. (2) Self-concept mediates these relationships; specifically, celebrity and online star endorsements activate the ideal and actual self respectively, and enhance consumers’ willingness to purchase. (3) The effect of endorsements on consumers’ purchase intention is moderated by advertising appeals. That is, celebrity endorsements enhance purchase intention when consumers are exposed to symbolic appeals in advertisements, and online star endorsements enhance purchase intention when it is matched with functional advertising appeals.